A survey of the Neotropical montane butterflies of the subtribe Pronophilina (Lepidoptera, Nymphalidae) in the Venezuelan Cordillera de la Costa - Viloria, Angel L.; Pyrcz, Tomasz W.; Orellana, Andrés (Zootaxa, 2010)
The fauna of montane satyrine butterflies of the subtribe Pronophilina (Lepidoptera: Nymphalidae) is surveyed in the Venezuelan Cordillera de la Costa, a long but relatively low range of mountains consisting of two parallel units, the northern and higher Serranía del Litoral and the southern, lower Serranía del Interior. The subtribe Pronophilina is briefly characterized. Twenty-three known species are listed and discussed. One new species, Eretris neocycla n. sp., and three new subspecies, Corades medeba pittieri n. ssp., Pedaliodes piletha costae n. ssp. and Pedaliodes manis ivica n. ssp., are described. Ten lectotypes are designated. Thiemeia phoronea obscurata Krüger is reinstated as a valid subspecies, based on female characters. Faunal affinities and local endemism ratio are evaluated. Alpha-diversity is discussed and compared with that of other South American ranges. Two elevational species assemblages are identified, lower and upper, the latter confined to the Serranía del Litoral.